U.P. research digest - Canieso, Asia G.; Marcial, Maria CorazonP; Perez, Anna Jhorie E.; Tolentino, Nanette M.; Uy, Jeanette P. (Education Research Program, University Center for Integrative and Development Studies, U.P., 1994)
This is part of a series produced by the UP-CIDS, which is biannual compilation of abstracts of completed research from the four autonomous campuses of the University. The first part features researches on different subject areas. The second part is constituted by the digest or research abstracts. The abstracts are arranged by campus, college, department, and alphabetically by author. Each entry consists of the name of the researcher, title of the research, year and abstract. An author-title index is provided. With this publication series, the editors aim to make these research accessible to people in and outside the university.